PENENTU PROFITABILITAS PADA BANK KONVENSIONAL YANG TERDAFTAR DI BEI TAHUN 2015-2017 - Eka Agustyn Nurhayati; Bambang Sudiyatno; Elen Puspitasari (Faculty of Economic and Business Universitas STIKUBANK, 2019)
This study aims to examine and analyze the effect of CAR, LDR and NPL on Profitability (ROE) at Conventional Banks listed on the Indonesia Stock Exchange in 2015-2017. The independent variables in this study are CAR, LDR and NPL. The dependent variable in this study is profitability (ROE).The sampling method uses purpose sampling at banking companies listed on the Indonesia Stock Exchange with the 2015-2017 period of 97 companies for 3 years to 97 data. The influence between variables is explained by using multiple regression analysis methods.The results showed that CAR had a significant negative effect on Profitability (ROE) on conventional banks listed on the Indonesia Stock Exchange in the 2015-2017 period. LDR has a significant positive effect on ROE on conventional banks listed on the Indonesia Stock Exchange in the 2015-2017 period. NPL has a significant negative effect on Profitability (ROE) on conventional banks listed on the Indonesia Stock Exchange in the 2015-2017 period. Keywords: CAR, LDR, NPL, Profitability.